Financial and ESG Determinants of Stock Prices: Evidence From IDX ESG Leaders - Marchia Azzahrah Putri; Isnawati Isnawati; Sarwani Sarwani; Rasidah Rasidah (Future Science, 2025)
This study aims to examine the influence of Return on Equity (ROE), Dividend Payout Ratio (DPR), firm size, and Environmental, Social, and Governance (ESG) factors on stock prices. The research focuses on companies listed in the IDX ESG Leaders Index during the 2021–2024 period. A purposive sampling method was employed, yielding a sample of 13 companies with a total of 52 firm-year observations. Data analysis was conducted using panel data regression with EViews 12 software. The empirical results reveal that Return On Equity and firm size have a positive and statistically significant effect on stock prices. In contrast, Dividend Payout Ration and Enviromental, Social, and Governance factors do not exhibit a significant influence. Theoretically, this study extends the literature by integrating financial performance indicators and ESG dimensions in explaining stock price variations within the Indonesian capital market. From a practical standpoint, the findings offer valuable insights for investors and policymakers in formulating investment strategies that balance financial fundamentals with sustainability considerations.